(untitled) (Architecture Image Studies, 2024)
Co-designed to celebrate the water cycle using ecological design principles, in situ/ Benfica H20 is a collaborative project involving academia, local authorities, and the community. It aims to address urban water cycle issues in public space, regarding its scarcity and excess, by fostering collective intelligence about the territory. Located in Benfica near Monsanto Forest Park, Cortiçada’s Garden is an underutilized public space with potential for community gathering as well as a place to combat climate change adversities. In response to the climate urgency, the project emerged from the fusion of scientific and empirical knowledge. A community of practice was established to create a new proposal for an existing, underused public space. The integration of architecture, engineering, and landscape architecture with local spatial perception was crucial for this initiative. Moreover, the project engages in dialogue with the municipality and local schools to explore how public spaces can be designed to prioritize sustainability. "Rain is also planted" is the motto of this intervention and is realized through a gravity-activated mechanism; when the water mirror reaches its maximum level, this water is conducted to the reservoir and then directed to a gravity-fed irrigation system that emulates artificial rain, thus watering the space renaturalized by the project. The proposal will reuse materials and a set of plant species from municipal nurseries, and the redesign of the garden was done in close collaboration with the community in co-design sessions. This planting plan was designed as a way to retain rainwater, and the design and construction of an art gallery over the water repository aim to establish a social contract of urban pedagogy, where the project serves as a learning vehicle about the different stages of the water cycle in an urban environment.